Teaching and studying social issues : major programs and approaches - Totten, Samuel; Pedersen, Jon E., 1960- (Emerald Publishing Limited : Information Age, 2010)
Teaching and Studying Social Issues: Major Programs and Approaches focuses on many of the major innovations developed over the past 100 years by noted educators to assist students in the study and analysis of key social issues that impact their lives and society. This book complements earlier books that address other aspects of studying and addressing social issues in the secondary classroom: Researching and Teaching Social Issues: The Personal Stories and Pedagogical Efforts of Professors of Education (Lexington, Books, 2006); Addressing Social Issues in the Classroom and Beyond: The Pedagogical Efforts of Pioneers in the Field (Information Age Publishing, 2007); and Social Issues and Service at the Middle Level (Information Age Publishers, 2009).The current book ranges in scope from Harold Rugg's pioneering effort to develop textbooks that purposely addressed key social issues (and thus provided teachers and students with a major tool with which to examine social issues in the classroom) to the relatively new efforts over the last 20 to 30 years, including global education, environmental education, Science/Technology/Society (STS), and genocide education. This book provides the readers with details about the innovators their innovations so they can (1) learn from past efforts, particularly in regard to what worked and didn't work and why, (2) glean new ideas, methods and approaches for use in their own classrooms, and (3) craft new methods and approaches based on the strengths of past innovations.